2021
DOI: 10.3390/plants10102228
|View full text |Cite
|
Sign up to set email alerts
|

Unique N-Terminal Interactions Connect F-BOX STRESS INDUCED (FBS) Proteins to a WD40 Repeat-like Protein Pathway in Arabidopsis

Abstract: SCF-type E3 ubiquitin ligases provide specificity to numerous selective protein degradation events in plants, including those that enable survival under environmental stress. SCF complexes use F-box (FBX) proteins as interchangeable substrate adaptors to recruit protein targets for ubiquitylation. FBX proteins almost universally have structure with two domains: A conserved N-terminal F-box domain interacts with a SKP protein and connects the FBX protein to the core SCF complex, while a C-terminal domain intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In Petunia hybrida, PhCS plays a crucial role in the synthesis of chlorophylls, carotenoids, and anthocyanins ( Masson et al., 2019 ). The F-BOX STRESS INDUCED (FBS) proteins have been associated with environmental stress networks, and WD40 repeat-like proteins are known targets of SCFFFBSI complexes ( Sepulveda-Garcia et al., 2021 ). The up-regulation of LOX, CS , and LOX3 genes suggested that BCP induced stress and damaged the metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In Petunia hybrida, PhCS plays a crucial role in the synthesis of chlorophylls, carotenoids, and anthocyanins ( Masson et al., 2019 ). The F-BOX STRESS INDUCED (FBS) proteins have been associated with environmental stress networks, and WD40 repeat-like proteins are known targets of SCFFFBSI complexes ( Sepulveda-Garcia et al., 2021 ). The up-regulation of LOX, CS , and LOX3 genes suggested that BCP induced stress and damaged the metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The F-BOX STRESS INDUCED (FBS) subfamily of plant FBX proteins has an abnormal structure, nevertheless, with an F-box domain placed in the center and extra conserved regions at the N-and C-termini. Sepulveda-Garcia et al [10] showed two WD40 repeat-like proteins in Arabidopsis that are highly conserved in plants and interact with FBS proteins, which were named FBS INTERACTING PROTEINs (FBIPs). FBIPs react only with the N-terminus of FBS proteins, and this interaction takes place in the nucleus.…”
Section: Variamentioning
confidence: 99%
“…These genes are collectively referred to as SLF genes in Solanaceae and Plantaginaceae or SFB genes in Rosaceae [31]. The N-terminus of SLF genes features an F-box domain, while the C-terminus possesses two highly variable regions (Hva and Hvb) that lack strong hydrophobicity and are primarily responsible for recognizing self and non-self S-RNase genes [32].…”
Section: Introductionmentioning
confidence: 99%